Smart Temperature Optimization of Devices used in Power Industries - Bhat, Ajaz Ahmad; Kaur, Kiranpreet (Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2021)
Temperature un-stability is the main problem faced in the industries like power and chemical plants that damage the number of devices used in these industries. To address these challenges the requirements is the optimized temperature control approach. Temperature is one of the foremost parameters to manage in most of the manufacturing industries like power stations, chemical, food method, pharmaceutical etc. In these forms of industries, some product would love the required temperature to be maintained at the highest priority the merchandise will fail. Microcontroller programming is a famous approach for making hardware devices instruction based. In this paper the authors deployed embedded programming to make an optimized and intelligent temperature controller system. How to cite this article: Bhat AA, Kaur K. Smart Temperature Optimization of Devices used in Power Industries. J Adv Res Alt Energ Env Eco 2021; 8(1): 12-15.